Nachhaltigkeitsrecht: Selbstverständnis, Status Quo und Perspektiven München 2022 - Bayer, Daria; Butz, Felix; Langlet, Franca; Poppe, Anna-Lena; Sommerer, Lucia M.; von Maltitz, Nicolai; Wöbbeking, Maren (Junges Nachhaltigkeitsrecht, 2023)
The volume of the Young Sustainability Law research network brings together contributions on the multi-layered relationship between law and the concept of sustainability. In particular, the focus is on the design and discussion of possibilities and conceptualizations of legal frameworks for a sustainable society - the sustainability law. The aim of the volume is to contribute to a multi-perspective and intra-disciplinary dialogue on the social, ethical, ecological, political, power-structural and economic implications of the current discourse on sustainability and the role of law in it. With contributions by Dr. Daria Bayer | Isa Bilgen | Katja Hamann | Ulrike Jürschik | Dr. Romy Klimke | Dr. Markus Lieberknecht | Prof. Dr. Anne-Christin Mittwoch | Marvin Reiff | Timo Vogle, LL.M. (London)